Comparison of Attitudes of Czech and English Teachers to Multicultural Subcompetencies - Hladík, Jakub; Jurtíková, Michaela (Wydawnictwo Naukowe UAM, 2013)
The study is a research probe into attitudes of Czech and English teachers regarding multicultural competence. The authors delineate theoretical foundations which defi ne multicultural competence and its possible further division. The aim of the empirical part of the study is to present the results of a comparative research probe aimed at identifying the importance attributed to particular multicultural competences by Czech and English teachers. The authors use a methodological approach in the interface of qualitative and quantitative research strategies, namely the Q-methodology. ANOVA was sed to determine differences in attitudes toward multicultural subcompetencies between Czech and English teachers. Furthermore, the Pearson correlation coeffi cient was used to analyse correlations between the groups of teachers.
Analiza porównawcza postaw czeskich i angielskich nauczycieli odnoszących się do kompetencji wielokulturowych
Keywords: multicultural competence; Q-methodology; multicultural education; intercultural competence; Czech teachers; English teachers